Migration in LDCs: Risk, Remittances, and the Family - Oded Stark (Finance and Development, 1991)
Labor votes with its feet-individuals migrate from areas of low wages to areas of higher wages. That has been the traditional view, one that has spawned much policy advice to control migration and to affect the location decisions of migrant laborers. But recent research indicates that portfolio investment theory might hold the key to understanding why people migrate in developing economies and how and why they remit their earnings. Under this theory, migration decisions are ordered by family needs for stable income levels, provided by a diversified portfolio of laborers, both male and female, and the need to jointly insure the family's well-being. In brief, group decisionmaking and objectives, rather than the wishes of individual migrants, determine migration patterns and remittance flows. This article, based on recent and earlier research by the author and his colleagues, attempts to explain migrant behavior in light of portfolio investment theory applied to field studies conducted in different parts of the world (see box on research). The results of the studies suggest a re-evaluation of policy approaches to migration and remittance issues.
Keywords: D1; D7; D81; G11; O12; O15; O21; R23; 330; Labor migration; Developing countries; Family decision-making; Risk-taking behavior; Portfolio investment theory; Remittances; Policy design